White death - Vicary, Tim (Oxford Univ. Press, 1998)
Sarah Harland is nineteen, and she is a prison. At the airport, they find heroin in her bag. So now she is waiting to go to court. Of the court decides that it was her heroin, then she must die. She says she did not do it. But if she did not, who did? Only two people can help Sarah: her mother, and an old boyfriend who does not love her now. Can they work together? Can they find the real crimonal before it is too late?